Urban river regeneration as a tool for healthy city planning: the case of Shenzhen Futian river - Zordan, Mirna; Zou, Junyu; Villani, Caterina; Talamini, Gianni (AESOP, 2019)
In the last decades, urban river regeneration (URR) has been increasingly adopted to solve environmental issues, especially in China. The prevalence of this trend is due in part to the fact that,besides solving water pollution problems, urban rivers are a potential new source of open publicspace for contemporary cities. Due to the extremely rapid urban development, available public space in these cities is shrinking and becoming more and more inadequate. In this context, URR can enhance the quality of the built environment, social life, and public health. This study aims to investigate the influence of URR on social life by analyzing people's behavior and perception of space. Due to its geographical location and its urban context, Futian River in Shenzhen has been chosen as a case study. Methods adopted include direct observation, interview, and survey research. The study is expected to explore the influence of urban river regeneration on social life, adding new knowledge for future healthy city planning in contemporary urban environments.
Keywords: urban river regeneration; open public space; human interactions; urban life